A Familiar Outbreak of Monophasic Salmonella serovar Typhimurium (ST34) Involving Three Dogs and Their Owner’s Children - Valeria Russini; Carlo Corradini; Emilia Rasile; Giuliana Terracciano; Matteo Senese; Federica Bellagamba; Roberta Amoruso; Francesco Bottoni; Paola De Santis; Stefano Bilei; Maria Laura De Marchis; Teresa Bossù (Pathogens, 2022)
Salmonella is a Gram-negative enteric bacterium responsible for the foodborne and waterborne disease salmonellosis, which is the second most reported bacterial zoonosis in humans. Many animals are potential sources of salmonellosis, including dogs, cats, and other pets. We report the case of an outbreak of salmonellosis in a family in central Italy, affecting two children and involving their three dogs as carriers. One of the children needed medical care and hospitalisation. Isolation and analysis of stool samples from the sibling and the animals present in the house were carried out. Serotyping allowed the identification of S. enterica subsp. enterica serovar Typhimurium in its monophasic variant for all the isolates. The results of whole-genome sequencing confirmed that the strains were tightly related. The minimum inhibitory concentration (MIC) test documented the resistance to ampicillin, sulfamethoxazole, and tetracycline. The origin of the zoonotic outbreak could not be assessed; however, the case study showed a clear passage of the pathogen between the human and non-human members of the family. The possibility of a transmission from a dog to a human suggests the need for further studies on the potential ways of transmission of salmonellosis through standard and alternative feed.